Probing new physics scenarios in accelerator and reactor neutrino experiments. (22nd April 2015) - Iura, A Di; Girardi, I; Meloni, D
Abstract: We perform a detailed combined fit to the disappearence data of the Daya Bay experiment and the appearance and disappearance data of the Tokai to Kamioka (T2K) one in the presence of two models of new physics affecting neutrino oscillations, namely a model where sterile neutrinos can propagate in a large compactified extra dimension and a model where non-standard interactions (NSI) affect the neutrino production and detection. We find that the Daya Bay ⨁ T2K data combination constrains the largest radius of the compactified extra dimensions to be μ m at 2 σ C.L. (for the inverted ordering of the neutrino mass spectrum) and the relevant NSI parameters in the range, for particular choices of the charge parity violating phases.